Analysis of Handling the Code of Ethics for Ad Hoc Supervisors in Constitutional Law - Oktafia, Wani; Marzuki, Marzuki; Akhyar, Adil (LPPPIPublishing, 2025)
Handling of ethical violations by Ad Hoc supervisors is in accordance with Article 3 Paragraph (2) of Bawaslu Regulation Number 4 of 2019 concerning the Mechanism for Handling Violations of the Code of Ethics of the District Election Supervisory Committee, Village/Sub-district Election Supervisory Committee, and Polling Station Supervisors. In this article, the Regency/City Bawaslu handles violations of the code of ethics committed by Ad Hoc supervisors. This study raises 3 (three) formulations of the problem, namely: first, What are the legal regulations regarding the code of ethics of election organizers according to the Law?, second, What is the Authority of the Regency/City Bawaslu in Implementing Bawaslu Regulation 4 of 2019? And third, How is the Implementation of Bawaslu Regulation 4 of 2019 by the Regency/City Bawaslu in the process of Handling Violations of the Code of Ethics of the Ad Hoc Election Supervisory Committee?. The research uses the nature of the research used is descriptive analytical, the type of research used in this study is normative juridical, the data collection tool in the research that will be used in this study uses Library Research. The data analysis used is by using a qualitative method that produces descriptive-analytical data. Based on the results of the study, with the delegation of authority from the DKPP given to their respective superiors based on DKPP Regulation No. 3 of 2017 as amended several times, most recently through DKPP Regulation No. 1 of 2021, the authority given by the DKPP to the Regency/City Bawaslu is in accordance with the constitutional law system in Indonesia.